Environmental Health Governance and Human Well-Being in an Urban Transport Terminal: Evidence from Mandalika Terminal, Mataram, Indonesia - Dania Hasim; Qisty Dita Amalia; Ifad Wijdan; Lalu Muhammad Aby Dujana; Ernawati Ernawati (Tinta Emas Institute, 2026)
Public transport terminals are high-exposure urban spaces where mobility, informal economic activity, sanitation, air pollution, noise, and public-service governance intersect. This study evaluated the implementation of five environmental-health principles at Mandalika Terminal, Sandubaya, Mataram, Indonesia, and interpreted the findings as indicators of passenger well-being, occupational exposure, urban service quality, and sustainable transport-tourism connectivity. A descriptive observational design was applied using field observation, structured interviews, questionnaires, checklist scoring, and direct measurements of wastewater, ambient air, and noise parameters. The overall environmental-health score was 73%, indicating good basic performance but incomplete exposure control. Wastewater management was generally adequate, with pH values of 7.40 and 6.79, water temperatures of 30.3 and 29.9 °C, and total dissolved solids of 917 and 138 ppm at the initial and downstream observation points, respectively. This condition was supported by closed drainage, the absence of visible stagnant water, and the absence of strong odour. Solid-waste management was also satisfactory because waste bins, waste segregation, routine collection, and relatively clean public areas were observed. Conversely, air and noise conditions were critical: PM10 (52 ug/m3), PM2.5 (504 ug/m3), CO (78 ppm), and noise (83.3 dBA) exceeded the operational benchmarks used in the assessment. Environmental-health education and community participation were present but remained dependent on static signage and informal compliance. The study shows that Mandalika Terminal has basic environmental-health capacity but requires stronger idling control, periodic emission testing, vegetative buffers, active education, waste standardisation, and cross-sector governance to protect passengers, workers, vendors, and tourists.